Time evolution of Cr and N on AISI 304 steel surface during pulsed plasma ion nitriding - Gomez, Bernardo Jose Armando (2003)
Chromium concentration on steels plays an important role in ion nitriding processes. In this work, the time variation of the concentration of the elements in the near-surface region of the AISI 304 (18% of Cr) stainless steel, during pulsed ion nitriding, was studied. The techniques used were the real time and in situ X-ray diffraction by Synchrotron radiation. Auger spectroscopy, Nuclear Reaction Analysis, and Conversion Electron Mossbauer Spectroscopy. Ion nitriding was performed with a 100 Hz square wave pulsed glow discharge, with different treatment times, in an atmosphere of 80% N and 20% H mixture, under a total 2 2 pressure of 5.6 mbar. The high Cr concentration in the near surface layers (;17 A) and the intermediate ‘S’ phase formation ˚ were explained through the nitrogen ion sputtering during the ion nitriding process.